Ramie-PLA Composite Hollow Sections for EV Chassis: Development and Static Bending Test - Mustasyar Perkasa; Tresna Priyana Soemardi; Djoko Wahyu Karmiadji; Yudan Whulanza; Arief Setyawan; Rizky Pratama Mulyana; Arga Agung Nugroho; Wahyu Sulistiyo; Masripah Masripah; Ridho Dwimansyah; Makmuri Makmuri; Wely Pasadena; Olivier Polit (Automotive Experiences, 2025)
The increasing demand for sustainable and lightweight materials in the transportation sector, particularly in the context of electric vehicles (EVs), has accelerated the exploration of bio-based composites as viable alternatives to conventional structural materials. This study investigates the mechanical performance of hollow structural components fabricated from polylactic acid (PLA)-based composites reinforced with natural ramie fibers, targeting their application as chassis elements in urban electric vehicles. Emphasis is placed on replacing commercial steel hollow sections with environmentally benign alternatives that maintain mechanical integrity while offering additional functional benefits such as electrical non-conductivity. Three-point bending tests were conducted to evaluate the composite specimens' flexural strength, stiffness, and failure behavior to assess structural viability. This method was selected for its relevance to real-world bending stresses encountered in vehicular chassis components and suitability for consistent evaluation across beam-like geometries. Results demonstrate that the ramie-PLA bio-composite exhibits promising flexural performance, with sufficient bendability and stiffness for potential structural integration. Furthermore, the non-conductive nature of the composite presents a significant advantage for reducing electromagnetic interference with sensitive electronic systems common in EV platforms. The findings support the feasibility of deploying natural fiber-reinforced PLA composites as a sustainable, cost-effective solution for lightweight automotive structures, particularly in emerging markets where urban EV adoption is rapidly expanding.